(untitled) (Modern education and development, 2025)
The article shows the determination of the compliance of the cargo with the dimensions and the permissible loads on semi-open wagons and platform elements in railway transport during the delivery of goods. Rolling stock for freight transportation is studied, measures and proposals for their selection are developed. In addition, the technical characteristics of the main models of wagons are analyzed, and proposals are made on the permissible loads on semi-open wagons and platform elements to eliminate the shortcomings of the existing system.